FIGURATIVE LANGUAGE IN REY’S BORN TO DIE AND ITS REFLECTION OF STERNBERG’S TRIANGULAR THEORY OF LOVE - Saputri, Ana Andriyani; Nurhamidah, Idha; Wulandari, Diyah Fitri (SIGEH ELT : Journal of Literature and Linguistics, 2025)
This study examines the lyrics of Lana Del Rey's album "Born to Die" (2012) as a literary text rich in figurative language and explores how they represent the three components of love—intimacy, passion, and commitment—in Sternberg's Triangle of Love Theory. The study focuses on the dominant types of figurative language—personification, metaphor, simile, hyperbole, metonymy, litotes, and irony—and maps their meanings to the theme of love in the album. The approach used is qualitative, using a close reading technique of the lyrics, followed by data collection (listening to and reading the lyrics), identification, classification based on the type of figurative language and its relationship to Sternberg's components of love, and data reduction to select the most relevant data. The primary data source is the album's lyrics, while secondary data includes theoretical references on figurative language and Sternberg's theory of love. The research limitation strictly excludes non-lyrical musical elements (vocals, arrangements, instruments) so that the analysis is focused on the lyric text as the object of linguistic-literary study. Theoretically, this research is expected to enrich stylistic studies on popular music; practically, the research provides an analytical model that connects figurative language devices in lyrics with the emotional dimensions of love according to Sternberg.